Percutaneous Stereotactic Radiofrequency Lesioning for Trigeminal Neuralgia: Determination of Minimum Clinically Important Difference in Pain Improvement for Patient-Reported Outcomes. Issue 3 (12th December 2013) - Reddy, Vishruth K.; Parker, Scott L.; Lockney, Dennis T.; Patrawala, Samit A.; Su, Pei-Fang; Mericle, Robert A.
Abstract: BACKGROUND: The Visual Analog Scale (VAS) and the Barrow Neurological Institute Pain Scale (BNI-PS) are 2 patient-reported outcome (PRO) tools frequently used to rate pain from trigeminal neuralgia (TN). Outcomes studies often use these patient-reported outcomes to assess treatment effectiveness, but it is unknown exactly what degree of change in the numerical scores constitutes the minimum clinically important difference (MCID). MCID remains uninvestigated for percutaneous stereotactic radiofrequency lesioning (RFL), a common surgical procedure for TN. OBJECTIVE: To determine MCID values for the VAS and BNI-PS in patients undergoing RFL. METHODS: Forty-three consecutive patients with TN who underwent RFL by a single surgeon were prospectively assessed with the VAS and BNI-PS preoperatively and 3 years postoperatively. Three anchors were used to assign each patient's outcome: satisfaction, willingness to have the surgery again, and Health Transition Index. We then used 3 well-established, anchor-based methods to calculate MCID: average change, minimum detectable change, and change difference. RESULTS: Patients experienced substantial improvement in both VAS (9.81 vs 3.35; P < .001) and BNI-PS (4.95 vs 2.44; P < .001) after RFL. The 3 MCID calculation methods generated a range of MCID values for each of the PROs (VAS, 4.13-8.20; BNI-PS, 1.03-3.30). The area under the receiver-operating characteristic curve was greater for BNI-PS compared with VAS for all 3 anchors, indicating that BNI-PS is probably better suited for calculating MCID. CONCLUSION: RFL-specific MCID is variable on the basis of the calculation technique. With the use of the minimum detectable change calculation method with the Health Transition Index anchor, the minimum clinically important difference is 4.49 for VAS and 1.16 for BNI-PS after RFL for TN.